Pelatihan Penelitian Kualitatif dengan Aplikasi NVivo Bagi mahasiswa Sarjana Teologi dan PAK STT Ekumene - Yakub Hendrawan Perangin Angin (Sekolah Tinggi Teologi Gereja Kalimantan Evangelis, 2026)
Qualitative research training with the Nvivo application for undergraduate students of Theology and PAK at STT Ekumene Jakarta is a necessity for completing their final thesis assignments, where so far the most widely known and used is data processing with SPSS software for quantitative research and manual data processing for qualitative methods. Through this qualitative training with Nvivo software, the aim is not only to provide an understanding of how the NVivo software is useful but also how to use it and its benefits in supporting data processing from the collection of thesis research data so that the results are faster and more guaranteed. This training is in accordance with what is needed by the Bureau of Research and Community Service (BPPM) STT Ekumene Jakarta which targets that 6th and 8th semester students in the Undergraduate Theology and PAK Study Program have the knowledge and skills in processing qualitative research data with software. The method chosen is through training that contains an explanation of the importance of research with qualitative methods using NVivo software, in this case NVivo 12, accompanied by simulations and direct practice by students on their respective laptops. The training was quite effective where students were able to recognize the main features of the NVivo program to enter interview data and other necessary data.